Proposta de uma Ferramenta para Elaboração e Monitoração de Aplicações Distribuídas - Gonçalves, Ronaldo Augusto de Lara; Akamatu, Durval Makoto; Gimenes, Itana Maria de Souza (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de Software, 1996)
The development of distributed applications enables either lightly loaded or idle processors to be grouped together for the execution of the same application, thus increasing applications speed up. This paper analyses the structures and resources of existing tools for the development of distributed applications in order to extract relevant concepts and techniques. Based on these information, a more simple tool is proposed which offers many interactive facilities to the user. The main techniques used are described showing the tool architecture and resources provided for distributed application programmers.